PERANCANGAN SISTEM INFORMASI LEGALISIR IJAZAH ONLINE DI POLITEKNIK NEGERI INDRAMAYU - Pramadhana, Dian; Febrianti, Kurnia Astrin; Farismana, Riyan; Ghozali, A. Lubis (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
An information system is a collection of interconnected elements that form a unity in integrating data, processing, storing and distributing information. Legalization is an attestation process by providing an original stamp and signature from the authorities on a photocopy of a diploma or grade transcript as proof that the photocopy matches the original diploma or grade transcript. The legalization process at the Indramayu State Polytechnic which is currently running is still done manually. This mechanism requires alumni who wish to legalize their diplomas or transcripts to come directly to campus. The legalization service system that is currently running at the Indramayu State Polytechnic is considered to be less effective because it takes a long time for alumni to process the application. Based on the problems above, the researcher aims to design a website-based information system for legalizing diplomas and transcripts. The legalization system is designed to focus on the needs of alumni and those from the academic department who are responsible for ratifying documents for legalizing diplomas and transcripts. The result of this research is a website platform for submitting online legalization requests which can help the academic section of the Indramayu State Polytechnic in managing legalization applications and make it easier for alumni to submit legalization applications.